2022
DOI: 10.1371/journal.pone.0272453
|View full text |Cite
|
Sign up to set email alerts
|

Coordinated decision-making boosts altruistic motivation—But not trust

Abstract: In the current study, we separately tested whether coordinated decision-making increases altruism and whether it increases trust. To this end, we implemented a paradigm in which participants repeatedly perform a coordinated decision-making task either with the same partner on every trial, or with a different partner on each trial. When both players coordinate on the same option, both are rewarded. In Experiment 1 (N = 52), participants were sometimes presented with tempting opportunities to defect. In Experime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…Knowing about the partner’s higher investment of effort increased participants’ commitment to the partner, which was manifested in greater persistence in a follow-up group task (Székely & Michael, 2018; Figure 1B). In a further study (Michael et al, 2021), repeated interaction led people to identify each other as ingroup members, thereby generating a sense of commitment to act in others’ interests—although this was not the case if participants believed that their partner had expressed a preference for a different partner (see also Chennells et al, 2022; Figure 1B). In a different set of studies, allocating participants to a minimal group, communicating about a group name, or coordinating in a die-roll game increased participants’ commitment toward a fellow group member (Zickfeld et al, 2023).…”
Section: Commitmentmentioning
confidence: 99%
See 3 more Smart Citations
“…Knowing about the partner’s higher investment of effort increased participants’ commitment to the partner, which was manifested in greater persistence in a follow-up group task (Székely & Michael, 2018; Figure 1B). In a further study (Michael et al, 2021), repeated interaction led people to identify each other as ingroup members, thereby generating a sense of commitment to act in others’ interests—although this was not the case if participants believed that their partner had expressed a preference for a different partner (see also Chennells et al, 2022; Figure 1B). In a different set of studies, allocating participants to a minimal group, communicating about a group name, or coordinating in a die-roll game increased participants’ commitment toward a fellow group member (Zickfeld et al, 2023).…”
Section: Commitmentmentioning
confidence: 99%
“…Such common goals are best described by the so-called joint commitment, as reviewed earlier, in which both agents are committed to each other based on the same action (Figure 1A). Indeed, commitment has been found to increase prosocial behavior (Chennells et al, 2022; Kokal et al, 2011; McEllin & Michael, 2022). For example, Kirschner and Tomasello (2010) found that joint music-making induced social commitment and prosocial behavior in 4-year-olds.…”
Section: Commitmentmentioning
confidence: 99%
See 2 more Smart Citations
“…An important factor in the renovation process is decision-making, which determines the overall direction. The renovation of old neighborhoods will require the participation of multiple decisionmaking bodies, and there are some contradictions between public and personal interests, information sharing, and information monopoly among different interest groups [5]. In addition, due to different interests, backgrounds, and knowledge reserved between the subjects, there will be differences in preferences between them in decision-making [6],…”
Section: Introductionmentioning
confidence: 99%